MANAGEMENT OF INFORMATION FLOWS IN A CYBERSECURITY SYSTEM - Fesenko, Andriy; Vyshnevska, Nataliya; Kozlovska, Diana (Ukrainian Information Security Research Journal, 2024)
Methods for controlling information flows in cybersecurity systems using probabilistic models and optimization algorithms have been studied. A mathematical framework has been developed for analyzing and stabilizing data flows in multichannel systems. Markov chains have been used to model the phase states of flows, and the information characteristics of the system, compression coefficients, and quasi-stationarity intervals have been mathematically estimated. The influence of tolerance parameters, phase state probabilities, and discretization levels on information transfer has been considered. Regularization mechanisms have been introduced to prevent singularities and ensure system stability. An adaptive approach to flow control has been proposed, allowing for dynamic adjustment of system parameters in the face of changing threats while maintaining the accuracy of data transmission.